2018
DOI: 10.1038/s41393-018-0200-1
|View full text |Cite
|
Sign up to set email alerts
|

Work and SCI: a pilot randomized controlled study of an online resource for job-seekers with spinal cord dysfunction

Abstract: Study design: Prospective, parallel randomized controlled trial (RCT) Objectives: To test the preliminary effects of an online resource targeted to job-seekers with spinal cord injury or disorder (SCI/D) and to determine the feasibility of proceeding to a full-scale RCT. Setting: Community cohort in Australia. Methods: Forty-eight adults (M = 42 years, SD = 10.95, 27 male) were randomized to receive 4-weeks access to the 'Work and SCI' resource (n = 25) or to a wait-list control group (n = 23). The 'Work and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…The following is a summary of the characteristics of the selected studies included in this review. 6,11,[22][23][24][25][26][27][28][29][30][31] The affiliated institution, country of origin, study title, study objectives, journals in which they were published, along with digital object identifier numbers and date of articles' first submission were extracted. After agreement by coauthors, studies were included, following independent search and screening efforts without the assistance of a librarian.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The following is a summary of the characteristics of the selected studies included in this review. 6,11,[22][23][24][25][26][27][28][29][30][31] The affiliated institution, country of origin, study title, study objectives, journals in which they were published, along with digital object identifier numbers and date of articles' first submission were extracted. After agreement by coauthors, studies were included, following independent search and screening efforts without the assistance of a librarian.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…21,25 Majority did not use ASIA scale classification, whereas some labeled participants as ''tetraplegia'' ver-sus ''paraplegia'' without detailed neurological levels. 11,22,24,27,28,30,31 Six studies reported completeness or incompleteness of injury. 11,22,24,27,30,31 One study that included MS participants reported only neurological levels of injury for its SCI participants.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations